The Influence of Parents’ Habits and Guidance on Fifth-Grade Elementary Students’ Languange Politeness at the Sultan Thaha Cluster in Pelepat Ilir - Taufik Muhtarom; Putri Wulan Ramadhani; Lutvi Alawiyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper investigates 1) the level of parents’ habits and guidance on students' language politeness, 2) the level of students’ language politeness, and 3) the influence of habits and parental guidance on students' language politeness. The research is quantitative research using a survey method. The research was conducted on 207 fifth-grade elementary students of Sultan Thaha Group Pelepat Ilir District. The sample used the Probabilistic Sampling technique with simple random sampling and was obtained from 136 students. The data collection techniques used questionnaires and documents, the research instrument testing consisted of validity and reliability testing, and the data analysis technique was descriptive analysis, and prerequisite tests consisted of normality and linearity testing and hypothesis testing using simple linear regression testing. The research results indicate that 1) the level of the parents’ habits and guidance was language politeness in the medium category, 2) the level of students’ language politeness was in the medium category, and 3) there was a significant influence between parents’ habits and guidance on students' language politeness. It is shown from the Anova table simple linear regression test table, which means that the calculated F value was 31,967 and the significance value was 0.00 < 0.05. Therefore, there is a significant influence of the variables of parents’ habits and parental guidance on students' language politeness.